Exploring the Local Wisdom Potential of Kerinci for Contextual Ethnochemistry Learning - Anzalina, Hofifah; Anggi Desviana Siregar; Indah Kencanawati (Orbital: Jurnal Pendidikan Kimia, 2024)
This study aims to explore the integration of local wisdom from Kerinci into chemistry learning by utilizing an ethnochemistry approach. The background of the research focuses on the importance of contextual learning in facilitating the understanding of chemistry concepts. The research method employed is a field study with a qualitative approach and descriptive design. The study involves chemistry teachers from SMA Negeri 7 Kerinci and the community of Koto Tuo Pulau Tengah village as informants. Data was collected through interviews, observations, and documentation. The data analysis technique applied is the Miles & Huberman model, which includes data reduction, data presentation, and conclusion drawing. The main findings of the research indicate that Kerinci's local wisdom, such as the use of turmeric, betel leaves, betel lime, jackfruit leaves, and banana peels, has significant relevance to chemistry material and can be integrated to enhance students' understanding. Teachers can create context-based lesson plans that link theoretical knowledge to practical examples, allowing students to grasp the real-world relevance of chemistry.